(untitled) - Sunderraman, Rajshekhar (Reading, Mass., 1999)
This programming companion from Rajshekhar Sunderraman is a streamlined approach to Oracle SQL, the most prevalent database language in industry and on campus. Focusing entirely on the necessary aspects of Oracle, it is designed as a specific guide for new users of this application. Using this primer in the classroom, students will be able to complete programming projects and assignments that use Oracle. These projects can be developed in a number of different programming environments (PRO*C, PL/SQL, and Oracle JDBC), thereby giving instructors flexibility and choice in these assignments
Keywords: Relational databases,SQL (Computer program language),PL/SQL (Computer program language),Ngôn ngữ lập trình SQL,Cơ sở dữ liệu quan hệ